STATUS OF MALOCCLUSION IN AURANGABAD DISTRICT OF MAHARASHTRA: A CROSS-SECTIONAL STUDY - B. Chavan, Bharat; S. Salve, Seema (International Journal of Psychosocial Rehabilitation, 2021)
Introduction: Millions of individuals worldwide are suffering from oro-dental problems, in spite most of them being preventable. Malocclusion is one of them. In a diverse and vast country like India, there exists a large variation in prevalence of malocclusion. This can be due to variations in ethnicity, nutritional status, religious beliefs, and dietary habits. To assign a treatment plan and to work out on the treatment needs of a particular group or population, it is mandatory to know the trends of occurrence of malocclusion. As there is a lack of statistical data on malocclusion in this particular geographical area, a study was conducted as suggested by WHO pathfinder methodology on 2400 individuals in Aurangabad district of Maharashtra to identify the distribution of malocclusion.Methods: A cross-sectional study was conducted among 2400 subjects in Aurangabad district by Rural Health Training Center, Paithan, under Govt Medical College, Aurangabad. The standard pro-forma was designed and house-to-house survey was conducted. All the findings were recorded in the data sheet after thorough intraoral examination. Descriptive statistical analysis and chi-square test were applied.Results: Prevalence of Malocclusion was found to be 55.59% in the present study.Conclusion: The baseline data is essential for planning dental public health programs and /or preventive orthodontic treatment programs. Further studies are encouraged to provide a more comprehensive understanding of the relationship between various sociodemographic factors and malocclusion